FUNCTIONALIZED POLYMERIC NANOPARTICLES: A NOVEL TARGETED APPROACH FOR ONCOLOGY CARE - RAIKAR, PRASIDDHI R.; M. DANDAGI, PANCHAXARI (International Journal of Applied Pharmaceutics, 2021)
Popular cancer therapies face extreme disadvantages, including multimedicament tolerance and non-target impact. These issues will lead to poorer patient conformity and poor levels of survival. Successful medical therapies for cancer patients are desperately required. Nano-particulate structures with a pluronic base represent revolutionary platforms for anti-cancer agent provision. These structures provide great potential for the advancement of cancer therapy due to their pharmacological properties and sufficient physicochemical characteristics. This review aims to offer a more detailed description of the pluronic drug delivery mechani sms that are currently available and explains pluronic as a medicinal polymer. Hydrophobic payload formulations and updated, targeted distribution mechanisms are explained based on pluronic formulations. This analysis offers a rundown of the current situation art related to the theranostic application of polymer micelles targeting the microenvironment of cancer cells. Some guidelines for the future scope and possible opportunities are also been addressed. Search criteria: Primary sources such as Medline a principal component of PubMed, an online, searchable, and biomedical and life science research literature database has been used. It brings readers to almost any area of interest with research and journal articles. One of the internet resources of importance to get scientific publications is specialized scientific search engines known as Google Scholar a database of research material that can be searched for. I have used the online electronic access portal of Elsevier, such as Science Direct to its publications. Scopus is the biggest abstract and peer-reviewed literature database for scientific journals, books, and conference work. Keywords like Cancer, Pluronic, Nanoparticles, Chemotherapy, Cancer, Theranostic, Targeted, Micelles, and Core-shell are crucial as they notify search engines of the content of the site. Range of years: 1992-2020.